Desain arsitektur sistem inspeksi produk cacat pada industri komponen otomotif berbasis IoT - R Arif Firmansah; Agus Anwar; Haryono haryono (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Indonesia is one of the countries with the largest manufacturing industry in ASEAN, related to the Making Indonesia 4.0 program, which is a government program to prepare for the era of the digital sector and smart factory, therefore innovation and sustainable development are needed in terms of technology , in the manufacturing industry, one of which is the automotive industry. . Factors that determine the success of the manufacturing industry and its components include being able to reduce the number of reject products in the production process. The purpose of this research is to design an architectural design of a defective product inspection system based on Internet of thingss technology , which allows the quality control department to obtain more objective data in a fast time and make decisions based on analytical data, the research methodology is observation and literature study. , the result of the research is the blueprint architect of the defective product inspection system in the automotive component industry with an Archimate modeling language, which shows that IoT technology can be designed to prevent company losses caused by rejected products and improve the quality of domestic automotive industry products